PERSEPSI DAN PENGALAMAN ORANGTUA TERHADAP PELAYANAN TUKANG URUT SEBAGAI ALTERNATIF PENGOBATAN : STUDI KUALITATIF - Salsabila, Aqiella Farida; Widiastuti, Komang; Pratama, Muhammad Yusril; Yoziana, Myra; Dharmadi Utama, Ricko; Shadiqi, Muhammad Abdan (Midwifery And Complementary Care, 2025)
Background: Traditional massage services are widely used by parents in Indonesia for minor health problems in children such as colds and fatigue. Influenced by cultural beliefs, this practice remains important despite modern medical advances. Riskesdas 2018 reported that 54.1% of South Kalimantan's population uses traditional health services, with 83.3% choosing massage therapy. This study explores the perception and experience of parents in using masseur services as an alternative treatment method. Objective:. To understand the motivations, benefits, and challenges that parents face in choosing massage services Methods: A qualitative approach with semi-structured in-depth interviews with five participants selected through purposive sampling. The data is analyzed thematically to identify key themes. Result: The findings revealed three main themes: (1) motivation for using massage services, which is based on cultural beliefs and previous positive experiences; (2) a comparison between massage services and modern medical services, which emphasizes accessibility, cost efficiency, and convenience; and (3) expectations for the development of professional and standardized massage services. Conclusion: Despite its limitations, traditional massage services have an important role to play in meeting the health needs of Indonesian families due to their affordability and accessibility. However, training and certification are required to improve the security and professionalism of these services. Keywords: Traditional Massage Practitioners, Alternative Medicine, Parental Perception, Safety, Professionalism